Preoperative assessment of the difficult airway in otolaryngology – implications for operative technique and airway management. - Milner, Analee (Operative Techniques in Otolaryngology - Head & Neck Surgery, 2020)
Despite a plethora of articles describing airway assessment, there is no magic bullet for difficult airway evaluation. Statistical validation of scoring systems and radiological evaluations appear to be elusive. The reason for our inability to reliably assess every airway is complex. Every airway has a subset of subtly different anatomical variables and when taken in totality may result in difficult bag mask ventilation or difficult intubation. Simply looking at 5-12 risk factors may not be relevant or adequate for an individual. Another possibility is that anatomical measurements of the airway may be difficult to standardize as exact anthropometrical landmarks may not be clear. And combined with the fact that unanticipated difficult bag mask ventilation or difficult intubation is rare (5.8%) some of the older studies may have been underpowered. A positive spin from extensive airway assessment research, coupled with heightened awareness of failed airway management and improved training and airway equipment, is that the need for invasive surgical airways has decreased. The future development of more sophisticated data algorithms could provide software whereby digital imaging techniques could be readily validated. Digital imaging is a technique whereby photographs or contrast-enhanced computerized axial tomogram scans are collated into 3D images, resulting in detailed customized evaluation. Until then, adherence to comprehensive, systematic, and rigid clinical approaches as described in this narrative review is obligatory, and complacency when managing any airway should be avoided.